Repair with a pulmonary neovalve in tetralogy of Fallot: does this avoid ventricular dysfunction?. (30th May 2022) - Guerrero, Albert Franz; Pineda-Rodríguez, Ivonne Gisel; Palacio, Andres Mauricio; Obando, Carlos Eduardo; Chalela, Tomas; Camacho, Jaime; Villa, Carlos; Umaña, Juan Pablo; Sandoval-Reyes, Nestor Fernando
Abstract: OBJECTIVES: Given the anatomical variations of tetralogy of Fallot (TOF), different surgical techniques can be used to achieve correction. Transannular patches (TAPs) are the most commonly used technique; they are associated with right ventricular dysfunction, the incidence of which can be reduced through pulmonary valve preservation. METHODS: Between January 2010 and July 2019, we performed 274 surgical corrections of tetralogy of Fallot at Fundación Cardioinfantil; 63 patients (23%) underwent repair with a TAP in addition to a pulmonary neovalve (Group I), 66 patients (24.1%) received a TAP without a pulmonary valve (Group II) and 145 patients (52.9%) had a repair with valve preservation (Group III). We analysed patient's characteristics before, during and after surgery at a 30-day follow-up. RESULTS: We found that patients in Group III were older ( P  =   0.04). Group II had the lowest level of O2 saturation before surgery (82%, P  =   0.001). Cardiopulmonary bypass and aortic cross-clamp times were longer in Group I ( P  <   0.001). Right ventricular dysfunction was less frequent in Group III (15.9%, P  =   0.011). Severe residual pulmonary regurgitation was more common in Group II (21.9%, P  =   0.001). CONCLUSIONS: Preservation of the pulmonary valve is an important factor for immediate postoperative management of tetralogy of Fallot. Patients who were repaired with a TAP with or without a pulmonary neovalve had a higher incidence of right ventricular dysfunction than those with pulmonary valve preservation. Abstract : Total repair of tetralogy of Fallot (TOF) is increasingly performed on neonates and infants.